Enhancing Politicians' Persuasiveness: Some Remarks on the Importance of Rhetorical Figures of Repetition in Political Discourse - Elżbieta Pieniążek-Niemczuk (Language, Culture, Politics)
The modern political class, which has been established on democratic principles both in Europe and America, is keen to use rhetoric and tools it provides. Any attempt to define the influence of these tools principally refers to the essence of rhetoric which is persuasion. Persuasion, on the other hand, is core to political discourse which, according to Teun van Dijk (1997, p. 14) is contextual, therefore must be recognized by its functions and/or goals. The functions of the discourse are often expressed in rhetorical devices and therefore play an important role in achieving political goals. The pieces of information presented in this article depict rhetorical devices as useful in increasing persuasiveness. Attention is paid to figures of repetition which constitute a universal category of rhetorical devices and thus need to be examined in a greater detail, especially in a discourse whose users focus their efforts on constructing efective persuasion.